Sintesis Komposit TiO2/Cu2O Menggunakan Metode Hidrotermal dengan Variasi Persen Massa TiO2 Terhadap Fotodegradasi Diazinon - Dimitry Febri Damayanti (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
This research studied and focused on the effect of TiO2 mass percent ratio on TiO2/Cu2O composite material synthesized by hydrothermal method. The mass percent ratio of TiO2 studied in this research is 0%, 20%, 35%, 50%, 65%, 80%, and 100% with TiO2 micropowder and Cu(CH3COO)2•H2O as precursor. The TiO2/Cu2O composites were prepared by hydrothermal method at 100˚C for 2 hours and then characterized by XRD, SEM, XRF, and UV-Vis DRS. The best diffraction pattern was shown by the 50% TiO2/Cu2O composite because it has the highest crystallinity, which is consistent with the anatase and cuprite crystal structures. The morphology of the TiO2/Cu2O composite is spherical and the variation of the mass percent of TiO2 which is getting bigger produces a smaller particle size. The variation of the mass percent of TiO2 which is getting bigger causes the number of Ti elements to increase and the number of Cu elements to decrease. The smaller TiO2 variations produce smaller band gap energy from 3.35 eV to 1.91 eV. The highest photocatalytic activity was produced by the 50% TiO2/Cu2O composite because it was able to degrade diazinon by 79.32% during an irradiation time of 120 minutes.
Reaploud Repository February_Hasyim
Keywords: TiO2/Cu2O Composites; Mass Percent Ratio; Hydrothermal; Photodegradation; Diazinon